Near-infrared imaging spectroscopy of IRAS FSC 10214+4724: Evidence for a starburst region around an active galactic nucleus at z=2.3 - Kroker, H; Genzel, R; Krabbe, A; TacconiGarman, L; Tecza, M; Thatte, N; Beckwith, S (1996)
We report 1″ imaging spectroscopy of the 1.95-2.4 μm wavelength region in the z = 2.284 galaxy IRAS FSC 10214+4724. We find that the rest-frame Hα and [N II] emission have different spatial extents. We also detect broad (ΔνFWZP ≈ 3500 km s-1) Hα emission. FSC 10214 is a very luminous gravitationally lensed galaxy, which intrinsically contains both a type 1 active galactic nucleus and a more extended star-forming disk. The AGN and circumnuclear star formation both contribute significantly to the total luminosity of ∼ 1013 L⊙. © 1996. The American Astronomical Society. All rights reserved.